Factors affecting value added disclosure of public listed companies in Singapore. - Cheong, Kok Wai. (2009)
Value added statements are concerned with the calculation and presentation of value added and how this is shared among employees, the government, the providers of capital and the company for future investment. The employees receive their share as wages and salaries and the providers of capital receive their share as either interest or dividends. The government receives its share through the payment of corporate tax. Finally, the amount provided for future investment is captured as retained profits and depreciation. Hence, the distribution of value added can be viewed as the returns to each of the contributing factors of production, defined in broad terms.